2013
DOI: 10.1002/abc.21118
|View full text |Cite
|
Sign up to set email alerts
|

Universal Design: A Tool to Help College Students with Asperger's Syndrome Engage on Campus

Abstract: Transitioning from high school to college is challenging for many students, but for none more so than students with Asperger's syndrome. Colette M. Taylor and Kathryn L. Colvin introduce the concept of universal design as an eff ective approach to supporting this increasing subpopulation of students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…We recommend that student affairs preparation faculty and supervisors role model the use of UD in a more intentional, systematic way. A number of best practice writings offer general suggestions UD implementation (Burgstahler, 2008), while others focus on specific functional areas (Vance et al 2014) or populations such as students with Asperger's syndrome (Taylor & Colvin, 2013). Our empirical findings provide support for UD literature that suggests all professionals have the responsibility and capacity to create services, programs, and environments that are useful and inclusive to all students, not just students with disabilities.…”
Section: Discussion and Recommendationssupporting
confidence: 61%
“…We recommend that student affairs preparation faculty and supervisors role model the use of UD in a more intentional, systematic way. A number of best practice writings offer general suggestions UD implementation (Burgstahler, 2008), while others focus on specific functional areas (Vance et al 2014) or populations such as students with Asperger's syndrome (Taylor & Colvin, 2013). Our empirical findings provide support for UD literature that suggests all professionals have the responsibility and capacity to create services, programs, and environments that are useful and inclusive to all students, not just students with disabilities.…”
Section: Discussion and Recommendationssupporting
confidence: 61%
“…The domain of academics involves processes for learning and using information. As students with ASD transition from high school to college, they face a number of academic challenges, including enhanced academic demands (Dente & Coles, 2012), difficulty with note taking (Sayman, 2015), and a general lack of academic services (Taylor & Colvin, 2013). Furthermore, students with ASD often struggle to advocate for needed services or supports.…”
Section: Barriers Associated With Five Domains Influencing College Sumentioning
confidence: 99%
“…In fact, many students with ASD report heightened levels of anxiety, loneliness, depression, uncertainty, and exhaustion, as compared with students without ASD (Dente & Coles, 2012; Van Hees et al, 2014). Unfortunately, college students with ASD often lack the skills necessary to cope with these challenging emotions (Taylor & Colvin, 2013). Although barriers related to the domains of academics, social interactions, living outside the family home, executive functioning skills, and mental health can hinder student progress, apps used on computers, tablets, or smartphones can support the successful transition of students with ASD to college.…”
Section: Barriers Associated With Five Domains Influencing College Sumentioning
confidence: 99%
See 1 more Smart Citation
“…This concept of using an electronic portfolio supports universal design for learning principles so all students have opportunities for learning/growing/creating using multiple forms of media. Taylor and Colvin (2013) found that universal design was an effective tool for helping college students with AS engage on campus.…”
Section: Feedback and Individual Reϐlections (20 Min)mentioning
confidence: 99%